PENGARUH KOMBINASI KAYU SENGON (Falcataria moluccana) DAN BAMBU PETUNG (Dendrocalamus asper) TERHADAP SIFAT FISIKA PAPAN LAMINASI - Wulandari, Febriana Tri; Amin, Radjali; Habibi; Ety Lisma, Ni Putu (Jurnal Penelitian Hasil Hutan, 2024)
Sengon wood can be strengthened by mixing with bamboo in making laminated boards.  The aim is to determine whether the combination of sengon wood and petung bamboo produces an increase in strength class and to determine the effect of pressure and weight on the physical properties of laminated boards made from sengon wood and petung bamboo.  The test results of the characteristics of physical and mechanical properties of the combination of sengon wood and petung bamboo resulted in an increase in strength class to strength class III according to JAS SE-7 2003 and SNI 01-6240-2000 standards. The felt pressure of laminated boards has a significant effect on moisture content and thickness development, but density and thickness shrinkage have no significant effect on the felt pressure of laminated boards. Adhesive weight significantly affected the physical properties of the board; adhesive weight and felt pressure together had no significant effect on the physical properties of the board.